The Making of Liquid Soap Based on Used Cooking Oil with An Addition of Starfruit Extract (Averrhoa Carambola L.) as an Antioxidant - Agustine, Dine; Nurlatifah, Ismi; Choirunnisa, Shaquariza Faiz Indra (BERKALA SAINSTEK, 2023)
The used cooking oil is a waste that can damage environmental sustainability if its disposed of directly without processing. One of the utilization of it, is as a raw material for making the liquid soap. Sweet starfruit (Averrhoa Carambola L.) is known have a potential as a source of natural antioxidants due to its high vitamin C content, flavonoid content and phenolic compounds. This study aims to determine the effect of adding sweet starfruit extract with variation of concentrations 8%, 10% and 12% on used cooking oil-based liquid soap and to analyze the characteristics of the resulting soap. The results showed that the organoleptic tests (shape, odor, color, water content and foaming power) met the SNI standards 06-3352-2016 which were quite good. The addition of sweet starfruit extract with a concentration of 12% was the most effective as an antioxidant.